Exposure To Infrared Rays Effectively Reduces the Total Germs on Eating Equipment in The Industrial Canteen - Rezkananda, Viyasa; Kahar, Kahar; Saputra Somad, Agus (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
Traditional food processing methods, unclean presentation and storage, and poor cutlery washing contribute to food-related diseases. The research occurred in an industry that transports oil and natural gas, fills LPG cylinders, and provides canteen facilities for workers to eat. According to Minister of Health Regulation No. 1096 of 2011, which pertains to Food Service Sanitation Hygiene, the permissible limit for the number of germs on cutlery surfaces is 0 colonies per cm2. The inspection results showed that the number of germs on the plate did not meet the recommended 321 colonies/cm2 threshold. We conducted this study to investigate the impact of varying infrared irradiation times on the number of germs on cutlery. The research was conducted using an experimental design, including a posttest and a control group, and involved three different irradiation time treatments: 10 minutes, 15 minutes, and 20 minutes, each with six repetitions. The study population consisted of 35 cutlery plates with a sample size 24. Data analysis was performed using the Kruskal-Walli's test, with results obtained at p <0.05 (0.000). After being irradiated for 10 minutes, 15 minutes, and 20 minutes, the average number of germs was 32 colonies/cm2, 11 colonies/cm2, and 0 colonies/cm2. The study's findings on reducing the number of germs in the industry were influenced by differences in the length of time for infrared light irradiation. It is recommended that sterilization cabinets be used in the industry to reduce the number of germs in industrial cutlery.